STRATEGI PENGEMBANGAN PESISIR PANTAI SELATAN SEBAGAI OBJEK PARIWISATA KABUPATEN KULON PROGO - Yayan Mulyana; Yuli anto (Journal of Tourism and Economic, 2019)
The coastal area of Kulon Progo Regency has a batik industry center that makes this batik unique enough that the Lendah sub-district. Bugel Beach Tourism in Galur Subdistrict is also a good tourist area to be enjoyed by tourists, there is a center of dragon fruit gardens in the bugel beach area to beautify the panoramas in Galur sub-district. Tourism development studies in these two sub-districts need to be carried out so that the development of the coastal tourism area in Kulon Progo area becomes more crowded and popular, so this research has the theme of the Strategy of South Coast Coastal Development as a Tourism Object of Kulonprogo Regency. Data processing technique using the SWOT analysis conducted to identify strengths, weaknesses, opportunities, and threats faced in the development of tourism in the coastal area of Sub Sub Lendah and Galur. A descriptive analysis was used to derive trends, developments, a comparison, in the management of the area The position of the southern coast (sub Galur and Lendah) as a region which will declare the tourist development program exists at the position among the high market growth due to tourism being one of the more improved and also more sights and position a strong competitive because there has been an object of interest in the vicinity which already stands.Thus the position of the South coast there are in quadrant I have match the tendency to carry out the following strategies managerial training effort for entrepreneurKey word: the coast, swot analysis, object tourism